ANALISIS KOMPARATIF DAYA SAING DOSEN DALAM MENGHADAPI ERA MASYARAKAT EKONOMI ASEAN (STUDI KASUS DOSEN FAKULTAS EKONOMI PADA PTS DI KOTA PALEMBANG) - Pandriadi, Pandriadi; Mario, Asma (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2018)
Facing ASEAN Economic Community (AEC) era, lecturers should prepare and increase their competitiveness to involve in a high competition. This research aims to analyze the comparation of competitiveness of lecturer based on gender, study program and education, a case study in Economic Faculty at some private universities in Palembang City. The competitiveness is measured by four indicators namely ability of English, ability to get funding for research, ability to get funding for community service and ability to publish articles in journal. By using quantitative method, this research tries to answer research questions particularly about lecturer competitiveness and comparative study between respondent based on gender, study program and education. Based on the analysis, this research conludes that the competitiveness of respondent majority is low, because from 100 respondent, 94 have low competitiveness, 4 have middle competitiveness and zero high competitiveness. In addition, by using statistic tools this research finds that there is no different of competitiveness level between male and female lecturer and also between lecturer in accounting and management study program. The researcher recommend that to increase competitiveness, the university should hold a sustainable English training for lecturers and also gives funding support to lecturer for doing researchs and community service programs.